ANALISIS PERVAL DAN CONSUMER EXPERIENCE TERHADAP MINAT PEMBELIAN PRODUK VIRTUAL DALAM APLIKASI FREEMIUM LINE WEBTOON DENGAN METODE PEMBAYARAN ELEKTRONIK (E-WALLET) SEBAGAI VARIABEL MODERASI - Liem Hana Junita Pratiwi; I Made Bayu Dirgantara; Afina Hasya (Diponegoro Journal of Management, 2022)
This research aims to know and determine how users of LINE Webtoon with their freemium business model, who felt the experience of reading comics freely as its core service can influence the user intention to purchase paid service (premium) which is fast pass and daily pass as an access for locked comic. Besides analysis on their experience, this research also analyzed on how users perceived the added value of those paid service the application offers in influencing users purchase intention. Purposive sampling is used for gathering data from those users who never use paid service on app. Questionnaires are distributed by Google Form to the population who aged 18-26 years old that also users of e-wallet services in daily basis and gathered 150 samples. Methods used to analyze data in this study is Partial Least Square (PLS) to test the outer model, inner model, and moderating effect, also hypothesis testing with t table test and path analysis. This study shows that there are no influences from perceived enjoyment, perceived social value, consumer experience and e-payment system (e-wallet) towards purchase intention to paid service on webtoon. There is a positive and significant influence coming from perceived quality as much 33,4% and perceived economic value as much 45,6% towards purchase intention. Moderating variable in this study e-payment system (e-wallet) is not significant to moderate the effect of all variables towards purchase intention.